Assessment of Growth and Yield Parameters of Sweet Flag (acorus Calamus L.) Accessions - Bhutia, K.G.; Sood, M.; Bhutia, P.L.; Kumar, V. (Indian Forester, 2024)
The ten different accessions of A. calamus L. were evaluated for their growth and yield parameters during the study with the aim to determine the accession which gives higher rhizome and essential oil yield under the midhill conditions of the Himalayas. Field experiments were conducted during the year 2015-16 and 2016-17at the experimental field of the Department of Forest Products, College of Forestry, Dr. Y S Parmar University of Horticulture and Forestry, Nauni, Solan (H.P.) with ten treatments. Fresh and healthy rhizomes of ten accessions of A. calamus L. were collected from Gujarat and several parts of Himachal Pradesh and planted in the field by following standard agronomic practices. Observations regarding different growth and yield parameters were recorded and statistically analyzed. It was revealed that most of the growth and yield parameters were significantly varied among the evaluated accessions during the present study. Based on two years average (2015-16 and 2016-17), maximum number of nodes/rhizome (25.82), rhizome length (13.24 cm), fresh rhizome weight (31.29 g/plant), dry rhizome weight (15.33 g/plant), estimated fresh rhizome yield (17.37 q/ha), estimated dry rhizome yield (8.51 q/ha), essential oil content in the fresh rhizome (1.07 %) and estimated essential oil yield (18.57 kg/ha) were observed in accession C4 compared to all other evaluated accessions.